2018
DOI: 10.1128/msphere.00499-17
|View full text |Cite
|
Sign up to set email alerts
|

Dating the Cryptococcus gattii Dispersal to the North American Pacific Northwest

Abstract: The recent emergence of the pathogenic fungus Cryptococcus gattii in the Pacific Northwest (PNW) resulted in numerous investigations into the epidemiological and enzootic impacts, as well as multiple genomic explorations of the three primary molecular subtypes of the fungus that were discovered. These studies lead to the general conclusion that the subtypes identified likely emerged out of Brazil. Here, we conducted genomic dating analyses to determine the ages of the various lineages seen in the PNW and propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 59 publications
(81 reference statements)
2
24
0
1
Order By: Relevance
“…Beside the antifungal activity of EOs and extracts of E. camaldulensis, it is worth noticing that this species, along with E. blakelyi M., E. gomphocephala A. DC, E. rudis Endl., and E. tereticornis Sm., is a reservoir of an emerging pathogenic fungus -Cryptococcus gattii. This fungus is usually related to tropic and subtropic regions, affecting the respiratory and nervous systems of the immunocompetent humans and domestic animals (Sorrell et al, 1996;Chakrabarti et al, 1997;Bielska and May, 2016;Roe et al, 2018). Similarily, C. neoformans var.…”
Section: Antifungal Effectmentioning
confidence: 99%
“…Beside the antifungal activity of EOs and extracts of E. camaldulensis, it is worth noticing that this species, along with E. blakelyi M., E. gomphocephala A. DC, E. rudis Endl., and E. tereticornis Sm., is a reservoir of an emerging pathogenic fungus -Cryptococcus gattii. This fungus is usually related to tropic and subtropic regions, affecting the respiratory and nervous systems of the immunocompetent humans and domestic animals (Sorrell et al, 1996;Chakrabarti et al, 1997;Bielska and May, 2016;Roe et al, 2018). Similarily, C. neoformans var.…”
Section: Antifungal Effectmentioning
confidence: 99%
“…More recent studies have suggested a South American origin of C. gattii where it is endemic, which makes the outbreak in the PNW exceptional given the temperate climate (33, 34). A 2018 study by Roe and colleagues estimated C. gattii was introduced to the PNW between 60 and 100 years ago, coinciding with the completion of the Panama Canal and the expansion of international shipping out of South America (35). However, C. deuterogattii VGIIb more closely aligns with isolates from Australia, suggesting multiple possible routes, sources, and introductions.…”
Section: Discussionmentioning
confidence: 99%
“…The Pacific Northwest emergence has been hypothesized to be related to the opening of the Panama Canal, enabling more shipping from eastern ports of South America to the West Coast of North America ( 5 ). The estimated timing of emergence of C. gattii in the southeastern United States occurred long before industrial shipping.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore applied the clonal mutation rate obtained from the prior Bayesian molecular clock analysis (using BEAST software [ 10 ]) of the Pacific Northwest C. gattii species complex, specifically for VGIIa and VGIIc (1.59 × 10 −8 SNPs/base/y). We determined the best-fitting clock and demographic model combination by implementing path and stepping stone sampling marginal-likelihood estimators as described previously ( 5 ). We implemented a general time-reversible nucleotide substitution model and an uncorrelated log-normal molecular clock with a Bayesian skyline model across 4 chains with 3 billion iterations and achieved across- and within-chain convergence.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation